ANALISIS PENGETAHUAN KEWIRAUSAHAAN, MOTIVASI KEPRIBADIAN, DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA - Asep Setiawan; Ady Kusuma Nurcholis; Sulastri Rini Rindrayani (BEMJ : Business, Entrepreneurship, and Management Journal, 2023)
Competition in the digital era makes students compete to create jobs in order to reduce unemployment. By paying attention to several factors in the surrounding environment. Examining students of the Faculty of Economics who majored in Management. The purpose of this study is to find out about the factors that influence entrepreneurial interest in students of the Faculty of Economics, Tulungagung University. This study uses Quantitative research methods. The population in this study were students of the Faculty of Economics, Tulungagung University, Class of 2020. The sampling technique used was Purposive Random Sampling with a sample of 76 students. The data collection technique was carried out by distributing questionnaires, and data processing using the SPSS 26.0 program application. The variables of this study are entrepreneurial knowledge, motivation, personality and family environment on entrepreneurial interest with Multiple Linear Regression analysis techniques.